2020
DOI: 10.1101/2020.05.15.098509
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of genetic background and gender on the increase in mitotic index in response to mating ofDrosophila melanogaster

Abstract: The replenishment of specialized cells depends on the activity of stem cells.Recent advances in stem cell research have shown that the germline stem cells (GSCs) in Drosophila melanogaster can increase their mitotic activity in response to mating. Here, we show that this ability to respond to mating is eliminated if the males are mutant for the ABC transporter, White, the genetic background for a plethora of fly lines. Furthermore, we were not able to reproduce previous findings that female flies increase thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Lastly, although our group has reported an increase in matinginduced female GSCs, other research groups have reported that post-mating increase in female GSCs has not been observed in their laboratories (Kao et al, 2015;Malpe and Schulz, 2020). Currently, we do not know the particular conditions that influence such discrepancies.…”
Section: Do Cryptic Genetic or Environmental Factors Induce Increase In Post-mating Increase In Germline Stem Cells?mentioning
confidence: 63%
See 1 more Smart Citation
“…Lastly, although our group has reported an increase in matinginduced female GSCs, other research groups have reported that post-mating increase in female GSCs has not been observed in their laboratories (Kao et al, 2015;Malpe and Schulz, 2020). Currently, we do not know the particular conditions that influence such discrepancies.…”
Section: Do Cryptic Genetic or Environmental Factors Induce Increase In Post-mating Increase In Germline Stem Cells?mentioning
confidence: 63%
“…However, in our experiments, we usually house 10-20 females with the equal number of males in one vial containing the standard cornmeal-dry yeast-sugar-agarose fly food without wet yeast paste. Authors Malpe and Schulz (2020) conducted their mating assay at 29 • C with yeast paste and apple juice as diet, while our group usually conducts the mating assay at 25 • C with a standard cornmeal-dry yeast-sugar-agarose fly food. Additionally, from the currently available literature, we cannot precisely compare the differences in diverse fly food recipes used in various laboratories.…”
Section: Do Cryptic Genetic or Environmental Factors Induce Increase In Post-mating Increase In Germline Stem Cells?mentioning
confidence: 99%